Papua under Joko Widodo's Administration: Implications for Australia-Indonesia Bilateral Relations [Papua di Bawah Pemerintahan Joko Widodo: Implikasi terhadap Hubungan Bilateral Australia-Indonesia - Floranesia Lantang (Universitas Pelita Harapan, 2022)
The issue of Papua is a “pebble in the shoe” for Indonesia. Unresolved past human rights violations, discrimination, and poverty remains the spotlight of countries especially the South Pacific Island, not to mention Australia. Given the complexity of this region, Joko Widodo (Jokowi) has done some progress in this Eastern most Provinces. Development and security become the center of Jokowi’s approach, while at the same time slowly progressing on human rights issue. This research will have a particular focus on the policies of Jokowi from his first to second period regarding Papua. Furthermore, this research will discuss the implication of Jokowi’s policies to Papua for Australia-Indonesia bilateral relationship. This research uses descriptive research method with two concepts from international relations: national security and human security. There are two main arguments derived from this topic: First, Jokowi’s approaches in Papua have shown Jakarta’s seriousness in developing Papua both from infrastructure and human resources sectors which aligned with national security and human security concept. Second, Australia must take an opportunity of Jokowi’s openness and approaches in Papua to at least addressing the reality and progress of this region for its public.Bahasa Indonesia Abstract: Isu Papua adalah